2014
DOI: 10.15252/emmm.201403868
|View full text |Cite
|
Sign up to set email alerts
|

ZIPCO, a putative metal ion transporter, is crucial for Plasmodium liver‐stage development

Abstract: The malaria parasite, Plasmodium, requires iron for growth, but how it imports iron remains unknown. We characterize here a protein that belongs to the ZIP (Zrt-, Irt-like Protein) family of metal ion transport proteins and have named ZIP domain-containing protein (ZIPCO). Inactivation of the ZIPCO-encoding gene in Plasmodium berghei, while not affecting the parasite's ability to multiply in mouse blood and to infect mosquitoes, greatly impairs its capacity to develop inside hepatocytes. Iron/zinc supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Regulation of iron is essential for cell survival and should also, therefore, be critical during the entire Plasmodium life cycle 23 24 25 26 . Iron withdrawal by the use of iron chelators has been explored as an antimalarial approach for decades 27 and novel compounds with improved pharmacokinetic properties are being investigated 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of iron is essential for cell survival and should also, therefore, be critical during the entire Plasmodium life cycle 23 24 25 26 . Iron withdrawal by the use of iron chelators has been explored as an antimalarial approach for decades 27 and novel compounds with improved pharmacokinetic properties are being investigated 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…2A) (Annoura et al 2014) and ZIPCO, an iron transporter expressed on the late liver stage PPM (Fig. 2B) (Sahu et al 2014). Although an increasing number of PV and PVM proteins have been identified that play important roles in liver stage development, an important future goal is the comprehensive identification of all liver stage PVM, PV, and PPM proteins that will supersede the current identification of important players using candidate approaches.…”
Section: Liver Stage Developmentmentioning
confidence: 98%
“…While not essential, it was found to be important to parasite development during the liver stage, and while transport function was not characterised directly, increasing extracellular iron could, in part, rescue P. berghei parasites in which ZIPCO was genetically disrupted [44]. The latter result, coupled with plasma membrane localisation, suggests that ZIPCO acts to import iron into the parasite [44]. The second is an orthologue of the vacuolar iron transporter, VIT, family, members of which are proposed to transport Fe 2+ into acidic vacuoles.…”
Section: Divalent Cation Transportmentioning
confidence: 99%
“…The first is an orthologue of the zinc/iron permease, ZIP, family (of which two exist in Plasmodium genomes), which is termed the ZIP domaincontaining protein, ZIPCO. While not essential, it was found to be important to parasite development during the liver stage, and while transport function was not characterised directly, increasing extracellular iron could, in part, rescue P. berghei parasites in which ZIPCO was genetically disrupted [44]. The latter result, coupled with plasma membrane localisation, suggests that ZIPCO acts to import iron into the parasite [44].…”
Section: Divalent Cation Transportmentioning
confidence: 99%